Moving Particle Semi-implicit Method in Simulating Water-Oil Penetration - Y Yulianto; Asril PA Mustari; Muhammad Ilham; A.N. Hidayati; S Hatmanti (Institut Teknologi Bandung, 2019)
In this study, the simulation of water-oil penetration has been performed by using the MPS method. The MPS method has been utilized to simulate the two-dimensional water-oil penetration and to observe the interaction of those liquids. This water-oil penetration phenomenon can be applied to the case of nuclear reactors. This study was performed to observe the liquid flow motion and its interaction between two different immiscible liquids with experiment and simulation. The obtained results of MPS method show an acceptable agreement with the experiment results. Those obtained results explain that the MPS method used in this study has a good enough capability to simulate the water-oil penetration phenomenon, which can be implemented in analyzing the melted reactor core.